2019
DOI: 10.1016/j.micres.2018.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Differential involvement of glycans in the binding of Staphylococcus epidermidis and Corynebacterium spp. to human sweat

Abstract: Sweat is a secretory fluid that can be a source of unpleasant body odour due to interaction of resident bacteria with sweat components. Identification of glycoproteins in sweat suggests that protein-conjugated glycans may act as binding epitopes for bacteria, as found in other secretory fluids such as human milk, tears and saliva which help to protect epithelial surfaces from infection.We conducted proteomic and glycomic analysis of sweat to reveal an abundance of glycoproteins, predominantly carrying bi-anten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…For example, the adhesion rate of S. epidermidis was much higher compared with Corynebacterium tuberculostearicum . Microorganisms differ in their adhesion mechanisms and often show a preference for certain host glycan moieties according to the specific affinities of microbial glycan-binding proteins or lectins on the cell surface ( 33 ). The fact that Corynebacterium species differ greatly in their ability to adhere to different mucus glycans ( 33 , 34 ) may provide an explanation for the lower adherence of Corynebacterium .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the adhesion rate of S. epidermidis was much higher compared with Corynebacterium tuberculostearicum . Microorganisms differ in their adhesion mechanisms and often show a preference for certain host glycan moieties according to the specific affinities of microbial glycan-binding proteins or lectins on the cell surface ( 33 ). The fact that Corynebacterium species differ greatly in their ability to adhere to different mucus glycans ( 33 , 34 ) may provide an explanation for the lower adherence of Corynebacterium .…”
Section: Discussionmentioning
confidence: 99%
“…Microorganisms differ in their adhesion mechanisms and often show a preference for certain host glycan moieties according to the specific affinities of microbial glycan-binding proteins or lectins on the cell surface ( 33 ). The fact that Corynebacterium species differ greatly in their ability to adhere to different mucus glycans ( 33 , 34 ) may provide an explanation for the lower adherence of Corynebacterium . SEM micrographs showed that not only live bacteria but also dead or damaged bacteria can adhere and interact with the epithelium ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above, a possible avenue for future research direction is from a recent investigation that reports sialic acid in other body fluids such as sweat. Results from that investigation examined the binding of skin bacteria to these ligands with the intent of identifying future therapeutic mechanisms to mitigate the effects of skin bacteria [34].…”
Section: Discussionmentioning
confidence: 99%
“…The binding assay was a modified version of a previous method. , The detailed procedure can be found in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%